Radiation characteristic of cylindrical dielectric resonator antenna simulation using CST microwave studio / Siti Zaharah Zakaria - Zakaria, Siti Zaharah (2006)
CST Microwave Studio is the new software that gives us choice between four powerful solver modules, the Transient Solver, the Eigenmode Solver, the Frequency Domain Solver and MOR solver, each offering distinct advantages in their own domains. But in this project, we are using Transient Solver to see the characteristic of the DRA. Besides the one dimensional, signal like results, CST Microwave Studio also allows to define many different 2D/3D monitors. And for every result type there is a variety of different plot options to visualize them. Cylindrical dielectric resonator antenna (DRA) using HEMng mode were examined using new 3D CST Microwave Studio to see the radiation pattern of the farfield, field distribution of the electric and magnetic field, resonant frequency and return loss of the DRAs. In this project, the radiation of cylindrical DRA is examined using four different structures, with three different positions of feed probe, CDRA that isolated in free space and CDRA with different permittivity.